Synthesis, Characterization and Biological Profile of Cationic Cobalt Complexes with First-Generation Quinolones - Alexia Tialiou; Antonios G. Hatzidimitriou; George Psomas (Molecules)
The interaction of cobalt(II) with first-generation quinolones oxolinic acid (Hoxo), flumequine (Hflmq), pipemidic acid (Hppa) and cinoxacin (Hcx) in the presence of the N,N′-donor heterocyclic ligands 2,2′-bipyridine (bipy) or 1,10-phenanthroline (phen) afforded a series of novel cobalt complexes, namely [Co(bipy)2(oxo)](PF6)2·H2O (1), [Co(phen)2(oxo)](PF6)2·0.5CH3OH·0.5H2O (2), [Co(bipy)2(flmq)](PF6)2·0.5CH3OH·0.5H2O (3), [Co(bipy)2(ppa)](PF6)2·CH3OH·0.5H2O (4), [Co(phen)2(cx)](PF6)2·CH3OH·0.5H2O (5), and [Co(phen)2(flmq)](PF6)·0.5CH3OH·H2O (6). The characterization of the complexes involved physicochemical techniques, various spectroscopies and single-crystal X-ray crystallography. The affinity of complexes to calf-thymus (CT) DNA was monitored with various techniques, suggesting intercalation in-between the DNA-nucleobases as the most probable interaction mode, which may be combined with electrostatic interactions as a result of the cationic nature of the complexes. The affinity of the complexes for bovine and human serum albumin proteins was monitored, and the determined corresponding albumin-binding constants revealed a tight and reversible interaction.